Management of the Jum’at Mengabdi Program in Developing Students’ Da’wah Skills at MAN 2 Langkat - Alfikri, Muhammad; Muchtar, Muhizar; Ridha, Zaifatur (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
This study examines the management of the “Jum’at Mengabdi” program in enhancing students’ preaching abilities at MAN 2 Langkat. The program is part of the Preaching Cadre Course (KKD) and is designed to provide structured training and practical preaching experience in the community. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model. The findings show that the management of the Jum’at Mengabdi program covering planning, organizing, implementation, supervision, and evaluation runs systematically and contributes significantly to the development of students’ cognitive, affective, and psychomotor preaching competencies. The program improves students’ mastery of preaching materials, public-speaking skills, confidence, and Islamic character. Effective coaching, scheduled practice, and community involvement are key factors supporting program success.